(untitled) (MEDICINE, PEDAGOGY AND TECHNOLOGY: THEORY AND PRACTICE, 2025)
This article reviews the history of pelvic inflammatory disease and provides information on how to prevent its spread. Epidemiological features of the disease, spreading factors and diagnostic methods were analyzed in the study. The main focus is on effective disease prevention measures, including vaccination, sanitation and public education. This article describes strategies to prevent pelvic inflammatory disease.